2012
DOI: 10.1016/j.combustflame.2012.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Visualization study of ignition modes behind bifurcated-reflected shock waves

Abstract: This study was a numerical and experimental investigation of lowtemperature auto-ignitions behind reflected shock waves in which a shock tube was employed as the experimental system. We used a high-speed video camera and the Schlieren method to visualize the ignition phenomena. Experiments were performed over a temperature range from 54910 to 134911 K and a pressure range from 56 to 203  kPa, and a non-diluted stoichiometric acetylene-oxygen mixture was chosen as the combustible gas. We introduced a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(20 citation statements)
references
References 27 publications
(45 reference statements)
0
20
0
Order By: Relevance
“…Lamnaouer et al also showed the presence of local hotspots in the wall jet after the passage of the bifurcation. Further simulations, such as those from Yamashita et al, 35 give evidence for hotspots in bifurcated flows. Combined with experimental schlieren results that indicate early ignition due to hotspots near the shock-tube walls, the numerical results of Yamashita et al 35 and Lamnaouer et al 31 give depth of understanding in determining the mechanism for this autoignition behavior.…”
Section: Experimental Nonidealitiesmentioning
confidence: 93%
“…Lamnaouer et al also showed the presence of local hotspots in the wall jet after the passage of the bifurcation. Further simulations, such as those from Yamashita et al, 35 give evidence for hotspots in bifurcated flows. Combined with experimental schlieren results that indicate early ignition due to hotspots near the shock-tube walls, the numerical results of Yamashita et al 35 and Lamnaouer et al 31 give depth of understanding in determining the mechanism for this autoignition behavior.…”
Section: Experimental Nonidealitiesmentioning
confidence: 93%
“…The authors analyzed experiments by Meyer and Oppenheim (1971a), Yamashita et al (2012), Penyazkov et al (2005) and their own simulations and found transition from weak to strong ignition in the shock bifurcation regime at Da bif ≈ 1 . In contrast to the previously introduced models, this approach does not involve chemical sensitivity parameters.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 97%
“…The authors found that this criterion reproduced experimental data at low pressure more accurately than the extended second explosion limit. Yamashita et al (2012) studied ignition modes in stoichiometric C 2 H 2 /O 2 at 56 kPa < p 5 < 203 kPa. The criterion by Meyer 85 and Oppenheim seemed to be applicable for C 2 H 2 /O 2 .…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…However, if solid boundaries are present, the reflection of a shock wave generates high temperature and pressure in which local auto-ignition, and possibly DDT can occur [38]. For example, a shock which reflects off an obstacle, or end-wall, will propagate backwards into the region of pre-heated, unburned gas between the lead shock and trailing deflagration [39].…”
Section: Detonation Initiation By Shock Reflectionmentioning
confidence: 99%